2022
DOI: 10.1186/s12903-022-02205-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of needle working length and root canal curvature on irrigation: a computational fluid dynamics analysis based on a real tooth

Abstract: Backgrounds To compare the irrigation efficiency with different needle working length and different root canal curvature based on a real unshaped root canal using computational fluid dynamics (CFD) method. Methods Images of the root canal of the maxillary first molar after being prepared to .04/15 were scanned using micro-CT, and then imported into the software for three-dimensional reconstruction. A palatal root canal with a curvature of 23.4° was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…The design of the MiC was based in previous studies 27 . Different geometries were created with each positive pressure needle (SV1, SV3, FV1, FV3, N1, N3); two different irrigation positions, 1 and 3 mm from WL, were chosen for each of them due to the influence of needle working length on irrigation results 32 ; and the MiC placed at WL following manufacturer's direction for use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the MiC was based in previous studies 27 . Different geometries were created with each positive pressure needle (SV1, SV3, FV1, FV3, N1, N3); two different irrigation positions, 1 and 3 mm from WL, were chosen for each of them due to the influence of needle working length on irrigation results 32 ; and the MiC placed at WL following manufacturer's direction for use.…”
Section: Methodsmentioning
confidence: 99%
“…Computational fluid dynamic (CFD) is a non‐invasive validated method to observe the behavior of irrigants and irrigation key magnitudes (wall shear stress ( τ w ), flow velocity, irrigant replacement and P a ) in the root canal system 30–32 . It allows the standardization of samples and reduce human errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that the wall shear stress distribution and the irrigant replacement in the root canal could be improved by locating the irrigation needles at the resorption level. Zhou et al 14 simulated the palatal roots of maxillary first molars with different root canal curvatures and found that the root canal with large curvatures was conducive to improving irrigation efficiency. Therefore, the use of simplified geometric shapes rather than a simulation of actual root canal anatomy may facilitate the analysis of irrigation efficiency, but it is not possible to obtain conclusions that can directly translate to clinical situations.…”
Section: Recent Cfd Analysis Of Root Canal Irrigationmentioning
confidence: 99%
“…Specifically, it can reach those minute regions in the root canal system so as to prevent microbial residue effectively, further improving the success rate of root canal treatment. In recent years, a large number of studies have found that many factors can affect root canal irrigation efficiency, such as the methods of root canal irrigation, 8 the types of root canal irrigation needles, 9 the depth of irrigation needle insertion, 10 the movement of irrigation needle, 11 the composition of irrigants, 12 the size of root canal preparation, 13 the curvature of the root canal, 14 and so on.…”
Section: Introductionmentioning
confidence: 99%